Features of clinical manifestations of generalized periodontal diseases in patients with diabetes mellitus type 2 - Lenihevych, Anna; Reshetnyk, Ljudmila (ScienceRise: Medical Science, 2025)
Aim: to establish the features of the configuration of generalized periodontal diseases and their clinical manifestations in the format of basic characteristics of type 2 diabetes mellitus. Materials and methods: Clinical, radiological and statistical methods were used. The subjects were 75 patients with type 2 diabetes mellitus, aged 19-44 years (mean age 26±3.8), who made up the main group (M), and 60 patients without signs of diabetes mellitus of a similar age - the comparison group (C). For a detailed analysis of the features of the clinical manifestation of GPD in patients with diabetes mellitus, all patients of the main (M) and comparison (C) groups were divided into several subgroups. M1 subgroup - patients with various forms of gingivitis. M2 subgroup was represented by patients with generalized periodontitis (GP) with type 2 diabetes mellitus as the underlying pathology. The comparative (C) group included two subgroups (C1), (C2) with different forms of gingivitis and periodontal disease, respectively. Results of our own studies. A high frequency of periodontal disease was diagnosed, reaching 100%, including both independent diseases of the periodontal soft tissues and all components of the periodontal complex, which was characteristic of all age groups and depended on the age of the patients, the duration and stages of type 2 diabetes. Periodontitis was mainly of stages I-II, chronic course prevailed over other stages of periodontal disease (80±4.6%). Radiologically, all patients, regardless of the severity of periodontal disease, had a characteristic vertical and horizontal type of resorption, pronounced osteoporosis of the bone component of the periodontal complex and expansion of the periodontal gap. The advantages and priorities of different segments of periodontal complex damage were traced in no case. For all patients with GP, a high degree of tissue sensitization to bone antigen was finalized, characterizing significant changes in the bone component of the periodontal complex in type 2 diabetes. A hypothesis of a plausible paradigm of the interdependence of GPD and type 2 diabetes as affiliated diseases was proposed as the first stage of further development of this direction. Conclusions: a direct relationship and interdependence of generalized periodontal diseases in the format of basic characteristics of type 2 diabetes have been established